Impact of ground motion characteristics on the seismic fragility of circular tunnels - Zhong-Kai Huang; Dong-Mei Zhang; Wu-Yu Zhang; Yong-Bo Li (Underground Space)
The seismic performance of tunnel structure can be examined by fragility analysis, which determines the probability that demand will exceed capacity for a given hazard intensity. Although it is commonly understood that earthquake uncertainties dominate fragility features, the implication of ground motion characteristics on the shield tunnel fragility analysis has not been comprehensively explored. Thus, this study aims to compare the effects of various earthquake characteristics on the fragility of the investigated shield tunnels. To this end, a typical shield tunnel was chosen and modelled using the finite element software. In addition, to account for typical ground motion characteristics, various ground motion sets, including near-field no plus motions (NFNP), near-field motions with a pulse (NFP), and far-field motions (FF), are selected, and a fragility analysis was assessed for every set of ground motion. The fragility curves were generated employing peak ground acceleration (PGA) as the intensity measure (IM) and tunnel drift as the damage measure (DM). The findings indicate that shield tunnels subjected to NFP may be more vulnerable compared to those subjected to NFNP and FF ground motions. This study’s findings highlight the vital role of ground motion characteristics in evaluating the fragility of shield tunnels. Moreover, the results may inform future seismic risk and resiliency evaluations regarding the importance of considering or disregarding the impacts of ground motion characteristics on tunnel vulnerability.